1996
DOI: 10.1182/blood.v87.4.1571.bloodjournal8741571
|View full text |Cite
|
Sign up to set email alerts
|

Primary mediastinal (thymic) B-cell lymphoma is characterized by gains of chromosomal material including 9p and amplification of the REL gene

Abstract: Primary mediastinal (thymic) B-cell lymphoma is a high-grade non- Hodgkin's lymphoma with unique features. By using comparative genomic hybridization and interphase cytogenetics, 26 tumors were analyzed to identify genomic imbalances. Gains of chromosomal material were much more frequent than losses (110 v 10) and involved chromosomes 9p, 12q, and Xq (31% to 50%). Interestingly, gain of Xq coincided with gain of 9p. Distinct high-level amplifications were found in four subregions. In 2 cases, amplifications of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(92 citation statements)
references
References 31 publications
8
82
2
Order By: Relevance
“…In line with our results, polysomy of chromosome 12 was detected as the most common abnormality in B-cell malignancies studied by fluorescence in situ hybridization (59). In addition, previous CGH studies reported gains and/or amplifications on 12q as recurrent aberrations in various types of non-Hodgkin lymphomas, including extracerebral DLBCL (3,5,6,22,35,55). A molecular genetic study reported amplifications of the proto-oncogenes GLI1, CDK4 and MDM2 (all located at 12q13-q15) in 11-14% of extracerebral DLBCL (43).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with our results, polysomy of chromosome 12 was detected as the most common abnormality in B-cell malignancies studied by fluorescence in situ hybridization (59). In addition, previous CGH studies reported gains and/or amplifications on 12q as recurrent aberrations in various types of non-Hodgkin lymphomas, including extracerebral DLBCL (3,5,6,22,35,55). A molecular genetic study reported amplifications of the proto-oncogenes GLI1, CDK4 and MDM2 (all located at 12q13-q15) in 11-14% of extracerebral DLBCL (43).…”
Section: Discussionsupporting
confidence: 89%
“…We identified one tumor with a high-level amplification of sequences from 9p23-p24. Amplification on distal 9p was previously observed in primary mediastinal B-cell lymphomas (22). Further evidence for a lymphoma-associated proto-oncogene at distal 9p comes from cytogenetic studies, which reported translocation breakpoints at 9p23-p24 in malignant lymphomas (40).…”
Section: Discussionmentioning
confidence: 75%
“…With regard to these findings, gains in 2p16 were most frequent in patients who failed to achieve a CR. It is noteworthy that a gain in chromosome 2p has been identified as a recurrent alteration in 20% of patients DLBCL 12,[31][32][33][34][35][36][37] and is the most frequent CGH alteration in classic Hodgkin lymphoma (identified in 50% of patients). 38,39 The common recurrent region expands 4.2 Mb in 2p15-16.…”
Section: Discussionmentioning
confidence: 99%
“…DNA microarrays have shown similarities between PMBL and cHL, suggesting that PMBL falls somewhere along the biological spectrum between NHL and cHL (Fig 4B;Rosenwald et al, 2003;Abramson & Shipp, 2005). In addition, several chromosomal aberrations found in PMBL, including gains in chromosome 9p [Janus kinase (JAK)-2] and 2p (c-Rel), are also amplified in cHL (Joos et al, 1996). PMBL is typically a malignancy of adolescents and young adults.…”
Section: Primary Mediastinal B-cell Lymphomamentioning
confidence: 99%